The application of FRAX values to determine the distribution of risk factors for Osteoporosis in Postmenopausal women - Irfani, Tri Hari (Public Health of Indonesia, 2016)
Background: Osteoporosis is the most common bone disease in humans that causes a bone fracture occurring without trauma or after a minimum trauma as complication. Aim: This study was to apply FRAX values to investigate the distribution of risk factors of osteoporosis in menopause in Palembang community.Methods: Cross sectional approach was applied in this study in order to know the distribution of risk factors for osteoporosis in postmenopausal women at Sub District in Palembang, Sumatera selatan, Indonesia. The study population was women who reside in Sub District of Palembang. Samples are all postmenopausal women in that sub district of Palembang with ages between 50-79 years. The sub district was randomly selected based on the completeness of population data to facilitate the conduct of research, and then carried out questionnaires to women after that the data on risk factors will be incorporated into the FRAX score to earn the percentage Major Osteoporotic and hip fracture for the next 10 years.Results: The value of major FRAX osteoporotic most often found in the percentage of <20% (108 people), while the value of FRAX hip fracture most often found in the percentage of <3% (90 people).Conclusions: women will have a risk to get possibility fracture that can be occurred in the next 10 years. It is required counseling and provision of basic knowledge to the public about the various risk factors associated with the incidence of osteoporosis. This includes lifestyle, physical activity and sport Key words: Osteoporosis, FRAX, Postmenopausal Women